The Use of Modified Rock Physics Template to Monitor Fluid Saturation in Carbonate Reservoir - Riskiray Ryannugroho; Sonny Winardhi; Djoko Santoso; Mohammad Rachmat Sule; Krishna Agra Pranatikta; Fernando Lawrens Hutapea; Dona Sita Ambarsari (Testing Center for Oil and Gas LEMIGAS, 2025)
Rock physics template (RPT) is defined as a crossplot of acoustic impedance (AI) against the ratio of P- and S-wave velocities that is used for lithology and pore-fluid interpretation of well log data and/or pre-stack seismic inversion results. This study is employing an interactive RPT approach, which facilitates calibration using available data and enhances the interpretation and prediction of pore fluids within carbonate reservoir rocks. A previously established RPT model is modified to construct the rock physics template and to interpret trends in porosity and fluid saturation within a predictive framework. The modified approach to the RPT formulation demonstrates that the proposed model yields more accurate porosity and fluid saturation trends for the reservoir rocks in the study area than the previous RPT model, as evidenced by the theoretical curves in the Rock Physics Template (RPT) domain. To predict fluid saturation, a workflow is developed to build the modified RPT model that incorporates the Curved Pseudo Elastic Impedance (CPEI) and the Pseudo Elastic Inversion for Lithology (PEIL) attributes. These attributes are used to regulate the fluid saturation and density values in the model space and to assist in constructing the RPT model. The proposed method is also applied to monitor fluid saturation changes in oil, gas, or CO₂ cases, utilizing the Vp/Vs ratio and acoustic impedance derived from the seismic inversion data, and allows calibration with available datasets such as well logs and cores.